2019
DOI: 10.3390/molecules24112035
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effect and Mechanism of Action of Honokiol on the Mouse Lipopolysaccharide (LPS) Depression Model

Abstract: There is growing evidence that neuroinflammation is closely linked to depression. Honokiol, a biologically active substance extracted from Magnolia officinalis, which is widely used in traditional Chinese medicine, has been shown to exert significant anti-inflammatory effects and improve depression-like behavior caused by inflammation. However, the specific mechanism of action of this activity is still unclear. In this study, the lipopolysaccharide (LPS) mouse model was used to study the effect of honokiol on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 74 publications
1
24
1
Order By: Relevance
“…This study was approved by the mice intended for guide cannula implantation into the skull were handled individually once daily for the 4 days before surgery, and then twice daily during the 2 days after recovery from anesthesia until the behavioral tests were performed. LPS was dissolved in sterile endotoxin-free isotonic saline and administered intraperitoneally on the first day at a dose of 1.2 mg/kg which dose is an adequate range for inducing the LPS-induced depressive-like behaviors [16] , [29] , [30] , [31] .…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the mice intended for guide cannula implantation into the skull were handled individually once daily for the 4 days before surgery, and then twice daily during the 2 days after recovery from anesthesia until the behavioral tests were performed. LPS was dissolved in sterile endotoxin-free isotonic saline and administered intraperitoneally on the first day at a dose of 1.2 mg/kg which dose is an adequate range for inducing the LPS-induced depressive-like behaviors [16] , [29] , [30] , [31] .…”
Section: Methodsmentioning
confidence: 99%
“…And activation of the inflammatory pathway in the brain reduces neurotrophic support and altered glutamate release/reuptake, as well as oxidative stress, leading to excitotoxicity, consistent with neuropathological findings of depression characteristics [ 27 ]. The proinflammatory cytokines can cause sickness behavior and cellular damage [ 28 , 29 ]. An increase of inflammation can lead to negative emotion, which was also supported by studies that induced inflammation through the injection of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol, a biologically active substance derived from the bark of magnolia trees, has been shown to exert significant anti-inflammatory, antioxidative, antitumour and neuroprotective effects [31][32][33]. Agacayak et al [34] found that treatment with 1 mg/kg honokiol for 14 days was effective in prevention of PAA in a rat model.…”
Section: Honokiolmentioning
confidence: 99%